78.8k views
4 votes
Solve for s. q=-6r+5s+3

User Cwick
by
6.1k points

2 Answers

5 votes

Answer:

s = q/5 + 6r/5 - 3/5

Explanation:

-5s + q = -6r + 3

-5s = -q - 6r + 3

s = q/5 + 6r/5 - 3/5

User Sagar Gala
by
6.0k points
6 votes

Answer: The required solution for s is
(q+6r-3)/(5).

Step-by-step explanation: We are given to solve the following equation for the value of s :


q=-6r+5s+3~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~(i)

To solve the equation for s, we should take s on the left-hand side and all other terms on the right-hand side of the equation.

From equation (i), we have


q=-6r+5s+3\\\\\Rightarrow 5s=q+6r-3\\\\\Rightarrow s=(q+6r-3)/(5).

Thus, the required solution for s is
(q+6r-3)/(5).

User Janderssn
by
5.8k points